Nonrelativistic treatment of fully-heavy tetraquarks as diquark-antidiquark states - Halil Mutuk (European Physical Journal C: Particles and Fields, 2021)
Abstract The goal of the present work is to obtain a reliable estimate of the masses of the ground and radially excited states of fully-heavy tetraquark systems. In order to do this, we use a nonrelativistic model of tetraquarks which are assumed to be compact and consist of diquark-antidiquark pairs. This nonrelativistic model is composed of Hulthen potential, a linear confining potential and spin-spin interaction. We computed ground, first, and second radially excited $$cc{\bar{c}}{\bar{c}}$$ c c c ¯ c ¯ and $$bb{\bar{b}}{\bar{b}}$$ b b b ¯ b ¯ tetraquark masses. It was found that predicted masses of ground states of $$cc{\bar{c}}{\bar{c}}$$ c c c ¯ c ¯ and $$bb{\bar{b}}{\bar{b}}$$ b b b ¯ b ¯ tetraquarks are significantly higher than the thresholds of the fall-apart decays to the lowest allowed two-meson states. These states should be broad and are thus difficult to observe experimentally. First radially excited states are considerably lower than their corresponding (2S-2S) two-meson thresholds. We hope that our study may be helpful to the experimental search for ground and excited $$cc{\bar{c}}{\bar{c}}$$ c c c ¯ c ¯ and $$bb{\bar{b}}{\bar{b}}$$ b b b ¯ b ¯ tetraquark states.